Searches for heavy Higgs bosons in two-Higgs-doublet models and for t → ch decay using multilepton and diphoton final states in pp collisions at 8 TeV - Khachatryan, V.; Sirunyan, A. M.; Tumasyan, A.; Adam, W.; Bergauer, T.; Dragicevic, M.; Eroe, J.; Fabjan, C.; Friedl, M.; Fruehwirth, R.; Ghete, V. M.; Hartl, C.; et al. (AMER PHYSICAL SOC, 2014)
Searches are presented for heavy scalar (H) and pseudoscalar (A) Higgs bosons posited in the two doublet model (2HDM) extensions of the standard model (SM). These searches are based on a data sample of pp collisions collected with the CMS experiment at the LHC at a center-of-mass energy of root s = 8 TeV and corresponding to an integrated luminosity of 19.5 fb(-1). The decays H -> hh and A -> Zh, where h denotes an SM-like Higgs boson, lead to events with three or more isolated charged leptons or with a photon pair accompanied by one or more isolated leptons. The search results are presented in terms of the H and A production cross sections times branching fractions and are further interpreted in terms of 2HDM parameters. We place 95% C.L. cross section upper limits of approximately 7 pb on sigma B for H -> hh and 2 pb for A -> Zh. Also presented are the results of a search for the rare decay of the top quark that results in a charm quark and an SM Higgs boson, t -> ch, the existence of which would indicate a nonzero flavor-changing Yukawa coupling of the top quark to the Higgs boson. We place a 95% C.L. upper limit of 0.56% on B(t -> ch).
Keywords: Astronomy & Astrophysics; Physics